PREFERENSI DAN TANGGAP FUNGSIONAL PARASITOID HEMIPTARSENUS VARICORNIS (GIRAULT) (HYMENOPTERA: EULOPHIDAE) PADA LARVA LALAT PENGOROK DAUN KENTANG - Hidrayani, Aunu Rauf, Soemartono Sosromarsono, dan Utomo Kartosuwondo. (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2009)
The preference and functional response of Parasitoid Hemiptarsenus varicornis (Girault) (Hymenoptera:Eulophidae) on host larvae of potato leafminers. The preference of Hemiptarsenus varicornis (Girault) on host larvae of potato leafminers (Liriomyza huidobrensis) and their functional response on host abundance were studied in laboratory. The preference test was conducted by releasing a female parasitoid in a cage containing two redbean leaves, one with 2nd instar and another one with 3rd instar. The functional response test was conducted by providing 3rd instar with density 1, 4, 6, 8, 10, and 13 larvae per leaf. The result showed that H. varicornis had the preference on 3rd instar larvae compared to 2nd instar, either for parasitisation or paralysis. Based on logistic regression analysis it was found that the parasitoid showed type II functional response on the increase of host abundance. The searching rate (a) and handling time (Th) for paralysis were 0.038 and 1.473 based on disk equation model, and 0.076 and 2.060 on ramdom equation model. For parasitisation activity, the value of a and Th were 0.012 and 4.649 based on disk equation model, and 0.014 and 5.075 on random equation model.